Diversity analysis in Hibiscus (Hibiscus spp.) germplasm - Koley, Tanushree; Majumder, Jayoti; Choudhuri, Tapas Kumar (Journal of Horticultural Sciences, 2025)
There is a wide array of germplasm availability in hibiscus throughout the globe. India, harbours a rich wealth of hibiscus, including H. rosa-sinensis, H. fragilis, H. storckii, H. schizopetalous, etc. These species serve as crucial repositories of genes responsible for various traits, including biotic and abiotic stress tolerance, colour intensity, petal arrangement, and hardiness. Safeguarding these genetic resources is essential for their utilization in future breeding programme. In this study, 19 hibiscus germplasm underwent precise classification based on 23 vegetative and floral characters following distinctness, uniformity, and stability (DUS) test guidelines of Protection of Plant Varieties and Farmers’ Rights Authority, New Delhi, India. Dissimilarity calculations, hierarchical cluster analysis, network plot analysis, and principal component analysis (PCA) were employed to assess the extent of diversity among the germplasm. The highest diversity was observed in variety June’s Joy. The hierarchical cluster analysis grouped the species into four major clusters, validated by linear discriminant analysis. Notably, Hibiscus rosa-sinensis germplasm grouped in the same cluster for flower colour. PCA results mirrored the dendrogram pattern, with June’s Joy standing out distinctly. While, no single morphological trait can singularly differentiate all germplasms, the collection of a comprehensive passport data incorporating various traits is imperative for advancing further studies in hibiscus genetic diversity and breeding programme.